The Legality and Challenges of Carbon Trading Implementation in Indonesia within the Framework of Presidential Regulation Number 98 of 2021 - Rival Pahrijal; Arief Fahmi Lubis; Muhamad Ammar Muhtadi (Westscience Press, 2026)
This study analyzes the legality and challenges of implementing carbon trading in Indonesia under Presidential Regulation No. 98 of 2021 using a normative legal approach. The regulation establishes the legal foundation for Carbon Economic Value (Nilai Ekonomi Karbon/NEK) instruments, including carbon trading, as part of Indonesia’s commitment to achieving its emission reduction targets under the Paris Agreement. Through a statutory and conceptual analysis, this research evaluates the coherence, clarity, and enforceability of the regulatory framework governing carbon trading mechanisms. The findings indicate that, normatively, carbon trading in Indonesia has a valid legal basis and reflects a progressive shift toward market-based environmental governance. However, several challenges hinder its effective implementation. These include regulatory fragmentation across sectors, overlapping institutional authorities, limited clarity in implementing regulations, and the underdevelopment of monitoring, reporting, and verification (MRV) systems. In addition, issues related to market readiness, stakeholder capacity, and alignment with international carbon trading standards further complicate the operationalization of the system. This study concludes that while the legal framework for carbon trading has been formally established, its practical effectiveness depends on further regulatory refinement, institutional strengthening, and improved coordination mechanisms. Strengthening legal certainty and enhancing implementation capacity are essential to ensure that carbon trading can function as an effective instrument for climate change mitigation in Indonesia.